From global mindset to international opportunities: the internationalization of Chinese SMEs - He, Chuantian; Baranchenko, Yevhen; Lin, Zhibin; Szarucki, Marek; Yukhanaev , Andrey (Journal of Business Economics and Management, 2020)
Following China’s “One Belt One Road” global economic expansion strategy, Chinese small and medium-sized enterprises (SMEs) along with state-owned, large corporations are increasingly seeking business opportunities internationally. Little is known about the process of small firms’ international opportunity creation and discovery in this particular context. This study examines the role of Chinese SME manager’s global mindset in driving their international opportunity identification through two key activities in their internationalization process: international knowledge based and networking activities. Data were collected from a survey of 191 small and medium-sized enterprises in China. The results of structural equation modelling show that Chinese SME managers’ global mindset has a positive effect on both international networking and knowledge acquisition activities, which in turn have positive effects on the development of international opportunities. The findings suggest that SMEs, while going through the internationalization process, rely extensively on social interaction with foreign business partners to obtain knowledge of the customers and institutions in the foreign market.